Complete mitochondrial genome of Pterodecta felderi (Lepidoptera: Callidulidae). Issue 3 (2nd July 2020) - Lee, Keon Hee; Kim, Min Jee; Park, Jeong Sun; Kim, Iksoo
Abstract: We report the mitochondrial genome (mitogenome) of Pterodecta felderi (Callidulidae: Lepidoptera), which is the first mitogenome sequences in the family Callidulidae, a monotypic family in the superfamily Calliduloidea. The 15, 340-bp long complete mitogenome consists of a typical set of genes (13 protein-coding genes [PCGs], 2 rRNA genes, and 22 tRNA genes) and 1 major non-coding A + T-rich region, which are arranged in a way that is frequently observed in Lepidoptera. Of the 13 PCGs, 12 P. felderi start with ATN, except for COI, which starts with CGA. The P. felderi mitogenome consists of 210-bp long intergenic-spacer sequences and 27-bp long overlaps. Phylogenetic analysis of superfamilial relationships in the lepidopteran clade Obtectomera with concatenated sequences of the 13 PCGs and 2 rRNA genes using the Bayesian inference method showed that Calliduloidea, which is only represented by P. felderi, was placed as the most basal lineage about Macroheterocera (Lasiocampoidea, Bombycoidea, Mimallonoidea, Noctuoidea, and Drepanoidea), Papilionoidea, and Pyraloidea.